Comparison of the clinical effect of unilateral transverse process extrapedicular and bilateral transpedicular percutaneous kyphoplasty for thoracolumbar osteoporotic vertebral compression fracture - Xu, Dingli; Ruan, Chaoyue; Wang, Yang; Hu, Xudong; Ma, Weihu (Frontiers in Surgery, 2024)
Background: Osteoporosis vertebral compression fractures (OVCF) become a common disease with the aging process. This study aimed to compare the effects of unilateral transverse process extrapedicular (UEPKP) and bilateral transpedicular (BTPKP) percutaneous kyphoplasty for thoracolumbar OVCF patients. Methods: Data of 136 OVCF patients treated with single-level PKP in our hospital from May 2019 to April 2021 were enrolled. Patients were grouped based on surgical procedure, 62 patients in UEPKP group and 74 in BTPKP group. All clinical and radiological data were collected from medical records. The clinical outcomes including visual analog score (VAS), Oswestry Disability Index (ODI), Japanese Orthopaedic Association Scores (JOA) of lumber were evaluated preoperative, postoperative, and at follow-up visit. The radiological evaluations (vertebral anterior height rate and local kyphosis angle) and complications were also collected. Result: All patients had successfully improved after operation. In UEPKP group, patients showed significantly short in operation time and less fluoroscopy frequency than BTPKP group (P<0.05). However, significant better distribution score and cement volume were found in BTPKP group (P<0.05). UEPKP group achieved significant better in VAS (0.6±0.5 VS 0.9±0.8) and ODI (24.7±3.1 VS 27.5±1.8) at final follow-up visit and BTPKP group (P<0.05). UEPKP group showed significant worse in radiological outcomes (Anterior height rate and local kyphosis angle) at 6-and 12-month follow up (P<0.05). As for complication, UEPKP group showed significant less in facet joint violation and intraspinal leakage (P<0.05). Conclusion: UEPKP could be safe and effective alternative procedure for patients with thoracolumbar osteoporotic vertebral compression fracture, which possess an apparent advantage in reducing intraspinal leakage and facet joint violation over BTPKP.